A review of Paratrichocladius Santos Abreu from the Sino-Indian Region (Diptera: Chironomidae: Orthocladiinae) - Fu, Yue; Sæther, Ole A.; Wang, Xinhua (Zootaxa, 2012)
Six new species of the orthoclad genus Paratrichocladius from the Sino-Indian Region (P. aduncus sp. n., P. bicinctus sp.n., P. caestus sp. n., P. comptus sp. n., P. sagittarius sp. n., P. ternarius sp. n.) are described and illustrated as males. Notesare given on P. ater Wang et Zheng, P. guidalii Rossaro, P. hamatus Wang et Zheng, P. lanzavechiai Rossaro, P.pierfrancescoi Rossaro, P. pretorianus (Freeman), P. rufiventris (Meigen), P. skirwithensis (Edwards), and P. tridens Fuet Wang based on Chinese material. The holotypes of P. mongolseteus Sasa et Suzuki, P. tobanonadecimus Kikuchi etSasa, P. tusimocedeus Sasa et Suzuki, P. unabrevis Sasa, and P. yakukeleus Sasa et Suzuki are re-examined. P. brevicornisand P. tamaater are listed. Paratrichocladius gotoefeus Sasa et Suzuki is transferred to the genus Paracricotopus and is ajunior synonym of Paracricotopus tamabrevis (Sasa et Suzuki). A key to the males of Paratrichocladius from the SinoIndian Region is given.